Alfred de Musset à l’Hôtel des haricots - Marine Lépinard (Itinéraires)
This article proposes to consider the publication process in the nineteenth century based on the echoes left by t a biographical event in literature: Alfred de Musset’s stay at the « Hôtel des haricots », the remand center of the National Guard, in September 1843. It examines the different writing gestures resulting from this incarceration, their reception and resonance in the print culture, and finally the materiality of a poetic writing, both configured by and configuring the place where it occurs. It will be the occasion to unfold the dialectic at work between various publications that contribute to narrate, describe, and represent the “Hôtel des haricots” as an artistic and literary place, their diversity and their complementarity. By evoking the overwhelming presence of the printed form in our research which is imposed by temporal distance, the article invites us to closely examine the texts by paying attention to the still perceptible echoes of their stories.